Establishing Effective Processes in Information Systems - Fikri, Abdullah Haikal (Journal of Renewable Engineering, 2025)
In the era of increasingly developing digital transformation, information systems (IS) no longer function only as administrative tools, but have become strategic components in supporting the sustainability and competitive advantage of organizations. This study aims to evaluate strategic planning of information systems using the Ward and Peppard methodology approach that emphasizes the alignment between business strategy and IS strategy. A descriptive qualitative approach with case studies is used in this study, with data collection through documentation studies and literature reviews. The analysis was carried out using various techniques, including SWOT, Value Chain, Critical Success Factors (CSF), Balanced Scorecard, McFarlan's Strategic Grid, and PEST. The results of the study indicate that the success of IS implementation is greatly influenced by a deep understanding of the organization's strategic needs and the use of appropriate methodologies to identify relevant IS applications. Ward and Peppard's methodology is able to provide a systematic framework for integrating information technology into business processes as a whole. Thus, IS strategic planning not only improves operational efficiency but also plays an important role in supporting the right decision making and the development of the organization's adaptive capabilities in facing the dynamics of the external environment. These findings provide an important basis for organizations in determining IT strategies that are aligned with long-term goals